Stimulation of Let-7 Maturation by Metformin Improved the Response to Tyrosine Kinase Inhibitor Therapy in an m6A Dependent Manner - Li, Kai; Gao, Shan; Ma, Lei; Sun, Ye; Peng, Zi-Yang; Wu, Jie; Du, Ning; Ren, Hong; Tang, Shou-Ching; Sun, Xin (Frontiers in Oncology, 2022)
The molecular mechanism of the tyrosine kinase inhibitor (TKI) resistant lung adenocarcinoma is currently unclear, and the role of methylated adenosine at the N6 position in the resistance of cancer stem cells (CSCs) therapy is unknown. We first confirmed the sensitization of Metformin enforcing on Osimertinib treatment, and revealed the mature miRNAs signatures of the Osimertinib resistant H1975 and HCC827 cells. Let-7b expression was stimulated when adding Metformin, and then increased the therapy sensitivity by decreasing the stem cells group expanding. Methyltransferase-like 3 (METTL3) increased the pri-Let-7b, decreased both the pre-Let-7b and mature Let-7b, attenuating the Let-7b controlling of stem cells renewal. In conclusion, we identified a novel and effective strategy to enhance the TKIs therapy response. The addition of Metformin increased the bindings of DNA methyltransferase-3a/b (DNMT3a/b) to the METTL3 promoter. With the help of the readers of NKAP and HNRNPA2B1, the cluster mediated m6A formation on pri-Let-7b processing increased the mature Let-7b, the key player to suppress the Notch signaling, and to re-captivate the Osimertinib treatment. We revealed the maturation processing signaling stimulated the methylation regulation of the miRNAs, and may determine the stemness control of the therapy resistance. Our finding may open up future drug development targeting this pathway for lung cancer patients.